Linking Emotion Management to Job Satisfaction and Performance: Evidence from University Lecturers in Jiangxi Province - Wu, Sitong; Sukirthanandan, Priya; Arkappan, Philominah (International Review of Management and Marketing, 2026)
This study examines the relationship between emotion management strategies, job satisfaction, and job performance among university lecturers in Jiangxi Province, China. Drawing on affective and organizational behavior perspectives, the study investigates whether lecturers’ use of surface acting, deep acting, and naturally felt emotions predicts job satisfaction and job performance, and whether job satisfaction mediates the relationship between emotion management and performance. A quantitative survey design was employed, and data were collected from 300 university lecturers across five universities in Jiangxi Province. Descriptive statistics, reliability analysis, correlation analysis, and hypothesis testing were used to examine the proposed relationships. The findings indicate that emotion management strategies significantly predict job satisfaction and job performance. Job satisfaction also has a significant positive effect on job performance and partially mediates the relationship between emotion management and performance. Among the emotion management strategies, deep acting shows a particularly important role in supporting positive work outcomes. The study highlights the importance of emotion regulation as a professional competency for university lecturers and suggests that higher education institutions should provide training and organizational support to strengthen lecturers’ emotional management, job satisfaction, and work performance.